INCREASED CAPACITY OF YOUTH THROUGH COMMUNICATION SKILLS IN THE VILLAGE OF BANDUNG REGENCY WARNASARI PANGALENGAN - Elly Komala; Yanti Susila Tresnawati; Winne Mardiani; Qisthy Rabathy (Pasundan International of Community Services Journal (PICS-J), 2019)
One of the large and important sector contribution in realizing the goals of national economic development is Youth. Youth have the ability to participate spur national economic growth. The development of small and medium enterprise sector that is managed by the Youth, especially in the village of Warnasari Pangalengan Bandung regency, West Java province. Warnasari village is actually located on a strategic area adjacent to the tourist potential Cileunca. Mountain air and natural beauty which is owned Warnasari, contributed to the development of the tourism sector. It can make Pangalengan Warnasari area as a tourism area.One community empowerment is very important to do in the village Warnasari is to prepare everything, both human resources and infrastructure to manage the natural resources that exist in order to boost the tourism potential there. Communication skills are also needed in relation -menjalin business development, marketing, promotion, etc. - also in the development and empowerment of self - personal branding / self empowering. Target outcomes of the implementation of this program is the creation of skills in verbal communication and non-verbal in both partners, The method used in the implementation of this program, covering namely; training and simulation. In addition to setting method, the team also determined the procedure, step - step. executive team is an expert in the field of environment Pasundan University Bandung, which is experienced in implementing development programs, especially in the field of communications. The most important thing in communication skills is understanding how to communicate in interaction, in this case the communication skills verbal and non-verbal is essential. Communication skills training people to participate actively in the interaction around it's precisely accurate. And indirectly Communication skills have become the main weapon which is powerful for people to be able to develop the tourism potential in the village Warnasari.